2019
DOI: 10.3390/min9100603
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Upper Yellow River as Revealed by Changes in Heavy-Mineral and Geochemical (REE) Signatures of Fluvial Terraces (Lanzhou, China)

Abstract: Despite decades of study, the factors that controlled the formation and evolution of theupper reaches of the Yellow River, including uplift of the northeastern Tibetan Plateau, Pliocene-Pleistocene climate change, and autogenetic processes are still poorly constrained. The stratigraphicrecord of such paleogeographic evolution is recorded in the sequence of nine terraces formed duringprogressive incision of the Yellow River in the last 1.7 Ma. This article investigates in detail forsediment provenance in terrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Envisaged paleogeographic scenario. In the Miocene, the paleo‐Yangtze and paleo‐Pearl River systems were established (He et al., 2019; Zheng, 2015), whereas the Huang He (Yellow River) may have not formed until the Pliocene (Wang, Nie, et al., 2019; Wang, Zhang, et al., 2019). Detrital garnet geochemistry and zircon geochronology concur to indicate that sediment deposited on the Chinese passive margin facing the present Taiwan Strait was largely derived from the paleo‐Yangtze.…”
Section: Provenance Of Western Taiwan Sandstones Assessed With Multimineral Approachmentioning
confidence: 99%
“…Envisaged paleogeographic scenario. In the Miocene, the paleo‐Yangtze and paleo‐Pearl River systems were established (He et al., 2019; Zheng, 2015), whereas the Huang He (Yellow River) may have not formed until the Pliocene (Wang, Nie, et al., 2019; Wang, Zhang, et al., 2019). Detrital garnet geochemistry and zircon geochronology concur to indicate that sediment deposited on the Chinese passive margin facing the present Taiwan Strait was largely derived from the paleo‐Yangtze.…”
Section: Provenance Of Western Taiwan Sandstones Assessed With Multimineral Approachmentioning
confidence: 99%
“…Researchers have also studied river basins and changes in certain components of the mineral composition over time in connection with heavy metals as a result of geological evolution. Wang et al [30] analyze sediment changes in the Yellow River (China), identifying nine river terraces created by the uplifting of the Tibetan Plateau and climate change through geologic history. Similar research is reported by Llena et al [31], who analyze the effect of geomorphological processes over time on mountain rivers.…”
Section: Introductionmentioning
confidence: 99%
“…The first article, by Wei Yue and co-authors of the Jiangsu Normal University (Xuzhou), Tongji University (Shanghai), Binzhou University (Binzhou) and Ludong University (Yantai) [10], is a quantitative analysis of textural and compositional modifications of detrital sediments used to unravel the sediment provenance and environmental changes in the Changjiang basin. The second article, by Zhao Wang and co-workers of diverse universities in China, United States, and Italy [11], investigates the early evolution of the upper reaches of the Yellow River based on heavy-mineral and REE geochemical signatures recorded in the sequence of nine terraces formed during the progressive incision of the Yellow River in the last 1.7 Ma. The volume is closed by the article by João Cascalho [12], a regional study of heavy minerals from the Portuguese continental margin, that points to the existence of contrasting sources, namely felsic igneous and metamorphic rocks and igneous basic rocks next to dolomitic limestones affected by thermal metamorphism.…”
mentioning
confidence: 99%